Advances in wearable textile-based micro energy storage devices: structuring, application and perspective. Issue 22 (8th October 2021) - Duan, Yixue; You, Gongchuan; Sun, Kaien; Zhu, Zhe; Liao, Xiaoqiao; Lv, Linfeng; Tang, Hui; Xu, Bin; He, Liang
Abstract : Wearable textile-based micro energy storage devices: construction, fundamental technique, functionalization. Abstract : The continuous expansion of smart microelectronics has put forward higher requirements for energy conversion, mechanical performance, and biocompatibility of micro-energy storage devices (MESDs). Unique porosity, superior flexibility and comfortable breathability make the textile-based structure a great potential in wearable MESDs. Herein, a timely and comprehensive review of this field is provided according to recent research advances. The following aspects, device construction of textile-based MESDs (TMESDs), fabric processing of textile components and smart functionalization ( e.g., mechanical reliability, energy harvesting, sensing, self-charging and self-healing, etc. ) are discussed and summarized thoroughly. Also, the perspectives on the microfabrication processes and multiple applications of TMESDs are elaborated.